TYPES OF INDONESIAN ABBREVIATIONS FOUND IN EKONOMI BISNIS RUBRIC OF PADANG EXPRESS NEWSPAPER - Jelvi Irawan, Saunir Saun, Rima Andriani Sari (English Language and Literature, 2012)
AbstrakThe purposes of this study were to (1) find the types of abbreviation found in Ekonomi Bisnis rubric of Padang Express newspaper, (2) know how the abbreviations constructed in Ekonomi Bisnis rubric of Padang Express neswpaper, published in February 2011 from edition 1 to editions 28 .This research used Weakly (2006) and Schendl (2001). Found 6 types, 5 types according to the theory of weakly and Schendl and 1 type not found. Into 5 types are: clipping word, blend, acronym, initialism, and contractions. While that is not included as it is a symptom of acronyms: PBB-P2 Taken From Pajak Bumi dan Bangunan Pedesaan dan Perkotaan.Key words: Newspaper, Word formation, Abbreviation, Types of Abbreviation.